Asymmetric effects of intra‐ and interspecific competition on a pond‐breeding salamander. Issue 6 (1st June 2015) - Anderson, Thomas L.; Whiteman, Howard H.
Abstract : A fundamental goal of evolutionary ecology is to understand how asymmetric competition influences phenotype expression, yet few studies have quantified the relative effects of intra‐ and interspecific competition on phenotypes. We examined the effects of intra‐ and interspecific larval competition on both discrete and continuous phenotype expression of the facultatively paedomorphic mole salamander ( Ambystoma talpoideum ). We manipulated the density and frequency of larval A. talpoideum and a common competitor, the spotted salamander ( A. maculatum ), in experimental mesocosms within a response surface design. The production of discrete ontogenetic morphs (metamorphs, paedomorphs, and overwintering larvae) was affected more by intraspecific than interspecific competition, but the effect varied between morphs. Paedomorph and metamorph production were more strongly affected by intraspecific than interspecific competition, while the production of overwintering larvae was affected by each type of competition approximately equally. Paedomorphs largely occurred only at low conspecific densities, overwintering larvae primarily occurred at high overall densities, and metamorph production peaked at intermediate densities of con‐ and heterospecifics. Density‐dependent intraspecific competition had stronger effects on body size and growth rates than interspecific competition for both metamorphs and overwintering larvae, whereas interspecific competition more strongly affected paedomorph size. Overall, these results support the hypothesis that intraspecific competition influences both continuous and discrete phenotypic expression more strongly than interspecific competition. Fluctuating strengths of each type of competition can affect variation in life history strategies by influencing discrete ontogenetic pathways via individual body sizes, leading to differential morph production and fitness within and among morphs.